Foundation phase teacher’s beliefs and perceptions about the importance of decolonising the South African foundation phase curriculum - Govindasami, Kathryn (My University, 2022)
This study seeks to investigate teacher’s beliefs and perceptions about the importance of decolonising the foundation phase curriculum in South Africa. The main objective of this research is to raise an understanding around decolonial thinking in teaching and learning, to contribute to the decolonial project focusing on foundation phase. Six foundation phase teachers were interviewed from one public primary school and one private school in Johannesburg. The teachers in this study taught from grades 1-3. The literature review is made of sections which explains existing literature based on the development of decolonial literature through the years and its importance for education. The focus is on decolonial theory emerging in response to postcolonial theory. Change is inevitable in education; thus, teachers would have to adapt to changing curriculum with new teaching and learning. Teachers on the ground have a meaningful role to lay in bringing change. This was a qualitative study as I focused on teacher’s beliefs and perceptions towards the concept of decolonising, especially the foundation phase curriculum. Individual semi-structured interviews were conducted with each teacher to ascertain their opinion without judgement. The findings of this study were surprising and extremely hopeful for our country. The study proved that teachers have an awareness of decolonisation, and they showed much approval toward integration of decolonial teaching and learning. Community, identity, and appreciation of indigenous knowledge that can build the South African child to be a truly well-educated and empowered citizen were some of the themes that emerged in this study
A dissertation submitted in fulfillment of the requirements of Masters of Education to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, 2022